Proceedings of the 2nd International Conference on Social and Political Development (ICOSOP 2017) 2018
DOI: 10.2991/icosop-17.2018.3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Harmony in Differences: increasing in universal difference orientation, sensitivity intercultural, thinking flexibility and prejudice.

Abstract: Abstract-This research has been started by testing the values of important batak culture and supporting variables of cultural learning process such as opennes, and cognitive flexibility towards increasing intercultural sensitivity among Batak students (Batak Toba, Batak Mandailing, Batak Karo, and Batak Simalungun ) in the city of Medan. The results of the study found that simultaneously all the variables play a positive and significant role in increasing the sensitivity between cultures to increase cultural s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
0
0
1
Order By: Relevance
“…It was suggested that the M-GUDS would be useful in creating and assessing interventions that focus on well-being within various settings, and that the development of the individual sub-constructs of UDO may be used to achieve overall well-being within these settings (Miville et al 2004). Nauly, Purba and Fauzia (2018) found positive results by using the M-GUDS to assess the effectiveness of their diversity training modules, having found that positive diversity attitudes are best formed over time and with continual interactions and engagement with diversity, which is also in alignment with various other studies that followed a similar route (Fu et al 2018;Kilgo 2015;Kohli et al 2016).…”
Section: Introductionsupporting
confidence: 63%
“…It was suggested that the M-GUDS would be useful in creating and assessing interventions that focus on well-being within various settings, and that the development of the individual sub-constructs of UDO may be used to achieve overall well-being within these settings (Miville et al 2004). Nauly, Purba and Fauzia (2018) found positive results by using the M-GUDS to assess the effectiveness of their diversity training modules, having found that positive diversity attitudes are best formed over time and with continual interactions and engagement with diversity, which is also in alignment with various other studies that followed a similar route (Fu et al 2018;Kilgo 2015;Kohli et al 2016).…”
Section: Introductionsupporting
confidence: 63%
“…Dengan kata lain, penelitian ini ingin menggali bagaimana identitas etnis orang Batak terbentuk, serta bagaimana proses psikologis yang kemudian terjadi hingga akhirnya membentuk identitas nasional. Penelitian ini juga meneliti secara spesifik dengan pendekatan kualitatif oleh karena kajian-kajian sebelumnya yang ditemukan menggunakan pendekatan kuantitatif (Crocetti dkk., 2013;Huddy & Khatib, 2007;Nauly, 2017;Spinner-Halev & Theiss-Morse, 2003;Stets & Burke, 2000).…”
Section: Tujuan Studiunclassified